Mast Cell Stabilizers as Host Modulatory Drugs to Prevent and Control Periodontal Disease - Dhoom Singh Mehta; Suhas Setty; Srinivas Sulugodu Ramachandra (Wolters Kluwer Medknow Publications, 2011)
Introduction: Mast cells are among the first cells to get in-volved in periodontal inflammation. Their numbers have been shown to be in-creased in cases of gingivitis and periodontal disease. The hypothesis: Since mast cell stabilizers like sodium cromogly-cate (SCG) and nedocromil sodium (NS) have been used in the prophylaxis of bronchial asthma without any significant adverse effects and also the fact that drugs like SCG show significant anti-inflammatory activities, it would be logical to use mast cell stabilizers as host modulating drugs for the treatment and prevention of peri-odontal disease. Evaluation of the hypothesis: Safety and efficacy of both SCG and NS are well documented. So, it will be systemically safe to use in humans. However, oral administration SCG or delivery of the drug by means local irrigation will not be very useful because SCG may not be secreted in the gingival crevicular fluid (GCF)(as in the case of oral administraion) or the drug may get washed out from periodontal pocket due to the constant flow of GCF(as in the case of irrigation). A local or targeted drug delivery of mast cell stabilizers can be used in patients with periodontal disease. Role of mast cells in periodontal disease has been dealt in-depth in many studies and articles. However, limited amount of research has been done on using mast cell stabilizers in the prevention and control of periodontal diseases. More studies are needed to study the efficacy and effective-ness of mast cell stabilizers as an adjunct to phase I therapy in the control of periodontal disease.